Prinsip Mu’asyarah Dalam Pola Relasi Keluarga Pengikut Jamaah Tabligh; Studi Lapangan Di Desa Wonodadi, Plantungan, Kendal - Khaidarullah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2020)
The pattern of relationship between husband and wife of Tablighi Jamaat can be considered as academic anxiety. That is, it should be addressed in-depth understanding of the complexity of the entity they are in the middle of the post-modern era is now before make a justification to them. With a phenomenological approach and the perspective of Islamic Family Law, the focus of this article is to describe the behavior of religious people in a particular community which is empirically as objective reality, and put analysis as attitudes toward academic beings respond to people's religious behavior problems scientifically and proportionately.